Enhancing Functional Foods with Plant Extracts: A Study on Gummy Candies Containing Sungkai Leaf Extract - Nurhasanah, Siti; Muhaimin; Pyopyash , Sverigenia Aprilia; Zaida; Pangawikan, Aldilla Din Pangawikan (Advance Sustainable Science Engineering and Technology, 2025)
Gummy candy is a popular food product, but it is generally high in calories and low in functional content. Sungkai leaves (Peronema canescens Jack) are known to contain antioxidant compounds that have the potential to be developed as functional food ingredients. To overcome the high calorie content of gummy candy, this study developed a low-calorie gummy candy formulation with the addition of encapsulated sungkai leaf extract and a low-calorie sweetener. This study aims to determine the optimal concentration of encapsulated sungkai leaf extract that produces gummy candy with optimal physicochemical, texture, antioxidant activity, and organoleptic characteristics. The study used an experimental method with Randomized Group Design (RAK), consisting of seven treatments of sweetener combination (xylitol and sucralose) and microcapsule concentration (3-7%). The results showed that the best formulation was a combination of 75% xylitol and 3% sungkai leaf extract microcapsules. This formulation produced good antioxidant activity (total phenolics 1,843 mg GAE/g; IC₅₀ of 597.878 mg/L), favorable texture (hardness 26.12 N; chewiness 42.99 Nmm), and good consumer acceptability (overall acceptability 3.71 out of 5). In addition, the caloric value was only 2.76 kcal/g, lower than conventional candy. The implications of the results of this study indicate a great opportunity for diversification of healthy food products based on local plants, as well as encouraging the development of functional food innovations that support a healthy lifestyle and prevention of degenerative diseases through the daily diet.